SRJ23, a new semisynthetic andrographolide derivative: in vitro growth inhibition and mechanisms of cell cycle arrest and apoptosis in prostate cancer cells - Wong, Hui Chyn; Wong, Charng Choon; Sagineedu, Sreenivasa Rao; Loke, Seng Cheong; Lajis, Nordin; Stanslas, Johnson (Springer, 2014)
Purpose 3,19-(3-Chloro-4-fluorobenzylidene)andrographolide (SRJ23), a new semisynthetic derivative of andrographolide (AGP), exhibited selectivity against prostate cancer cells in the US National Cancer Institute (NCI) in vitro anti-cancer screen. Herein, we report the in vitro growth inhibition and mechanisms of cell cycle arrest and apoptosis induced by SRJ23. Methods 3-(4,5-Dimethythiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay was used in assessing in vitro growth inhibition of compounds against prostate cancer (PC-3, DU-145 and LNCaP) and mouse macrophage (RAW 264.7) cell lines. Flow cytometry was utilised to analyse cell cycle distribution, whereas fluorescence microscopy was performed to determine morphological cell death. DNA fragmentation and annexin V-fluorescein isothiocyanate (FITC)/propidium iodide (PI) flow cytometry were done to confirm apoptosis induced by SRJ23. Quantitation of cell cycle and apoptotic regulatory proteins were determined by immunoblotting. Results AGP and SRJ23 selectively inhibited the growth of prostate cancer cells compared with RAW 264.7 cells at low micromolar concentrations; however, SRJ23 was more potent. Mechanistically, SRJ23-treated PC-3 cells displayed down-regulation of cyclin-dependent kinase (CDK) 1 without affecting levels of CDK4 and cyclin D1. However, SRJ23 induced down-regulation of CDK4 and cyclin D1 but without affecting CDK1 in DU145 and LNCaP cell lines. DNA histogram analysis revealed that the SRJ23 induced G2/M in PC-3 cells but G1 arrest in DU-145 and LNCaP cells. Morphologically, both compounds induced predominantly apoptosis, which was further confirmed by DNA fragmentation and annexin V-FITC staining. The DNA fragmentation was inhibited in the presence of caspase 8 inhibitor (Z-IETD-FMK). Apoptosis was associated with an increase in caspase 8 expression and activation. This thought to have induced cleavage of Bid into t-Bid. Additionally, increased expression and activation of caspase 9 and Bax proteins were apparent, with a concomitant down-regulation of Bcl-2 protein. Similar apoptosis cascade of events was observed in SRJ23-treated DU145 and LNCaP cell lines. Conclusion SRJ23 inhibited the growth of prostate cancer cells by inducing G2/M and G1 arrest via down-regulation of CDK1, and CDK4 and cyclin, respectively, and initiated caspase-8-mediated mitochondrial apoptosis. Taken together, these data support the potential of this compound as a new anti-prostate cancer agent.